2021
DOI: 10.1371/journal.pone.0255789
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the systematic review of the epidemiology of superficial Streptococcal A infections (skin and throat) in Australia

Abstract: Objective We have produced a protocol for the comprehensive systematic review of the current literature around superficial group A Streptococcal infections in Australia. Methods MEDLINE, Scopus, EMBASE, Web of Science, Global Health, Cochrane, CINAHL databases and the gray literature will be methodically and thoroughly searched for studies relating to the epidemiology of superficial group A Streptococcal infections between the years 1970 and 2019. Data will be extracted to present in the follow up systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This paper has not included several papers included in past systematic reviews. With reference to the published protocol several articles were reviewed by the research team, given their inclusion in previously published evidence [ 19 ]. Discussion concluded that Shelby et al should be excluded from this analysis as the reported prevalence of impetigo was amongst children already diagnosed with trachoma, potentially confounding prevalence results if children with trachoma were more or less likely to have impetigo [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This paper has not included several papers included in past systematic reviews. With reference to the published protocol several articles were reviewed by the research team, given their inclusion in previously published evidence [ 19 ]. Discussion concluded that Shelby et al should be excluded from this analysis as the reported prevalence of impetigo was amongst children already diagnosed with trachoma, potentially confounding prevalence results if children with trachoma were more or less likely to have impetigo [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review is reported according to the updated Preferred Reporting items for Systematic Reviews and Meta-Analyses (PRISMA) statement and the Meta-analysis of Observational Studies in Epidemiology (MOOSE) guidelines [ 16 18 ]. The search strategy and review protocol have been published elsewhere, and no amendments have been made [ 19 ]. This review included published and unpublished articles containing epidemiological data (incidence and prevalence) on the clinical presentations of a probable sGAS infection (impetigo/ skin sore/ pyoderma and/or pharyngitis/ tonsillitis) in English from the years 1970–2020 inclusive from Australian settings.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference in data collection may account for some of the discrepancies. We also believe that despite the existing gaps in knowledge, the growing importance of group A Streptococcus (GAS) skin infections as a precipitating factor for ARF in Australia and New Zealand, compared with strep-throat infections as the sole factor in our cases, might explain the differences in the rates of ARF across these case studies 7–9. Additionally, New Zealand only published data for 2 months during the pandemic 6.…”
mentioning
confidence: 92%